Hemodynamic Stroke in Simultaneous Cardio Cerebral Infarction: A New Term for Cardiologist - Yusuf, Mochamad; Pratama, Ivan Satria; Gunadi, Ruth; Sani, Achmad Firdaus (Open Access Macedonian Journal of Medical Sciences, 2021)
We report an uncommon case of simultaneous cardio-cerebral infarction, due to Inferior – right ventricle ST Segment Elevation Myocardial Infarction (STEMI) with acute ischemic stroke. Incidence of cardio cerebral infarction is exceptionally rare, with an incidence rate as low as 0.009%. Hemodynamic compromise in patients with acute myocardial infarction may result in the cerebral blood flow reduction that cause hemodynamic stroke. Due to the rarity of this condition, there were no recommended therapeutics strategy. Mechanical reperfusion with PCI procedure may be a superior choice in the settings of acute cardio-cerebral infarction for restoring hemodynamic stability.